Diarrhea in Cats Infected with Cystoisospora spp. - Evaluation of the Neutrophil-to-Lymphocyte Ratio and Monocyte-to-Lymphocyte Ratio - Tuna, Gülten Emek; Kirkulak, Tuğrul (Acta Scientiae Veterinariae, 2023)
Background: Cystoisospora spp. is considered a potential pathogen to cause diarrhoea in cats, and the disease occurs clinically, especially in young, weak and immunocompromised cats. The present study aimed to evaluate the clinical utility and diagnostic roles of neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte (MLR) ratios in diarrheal cats infected with Cystoisospora spp. Materials, Methods & Results: Twenty-five cats with diarrhea due to infection caused by Cystoisospora spp. and 15 healthy cats were included in this study. The anamnesis, clinical and laboratory findings of all cats were recorded. A clinical severity score was generated for diarrheal cats, which included activity, appetite, presence of vomit, and faecal consistency. Also, cats infected with Cystoisospora spp. were classified as systemic inflammatory response syndrome (SIRS) positive (+) and SIRS (-) group according to the presence of at least 3 of the SIRS criteria. The Cystoisospora spp. oocysts were diagnosed by direct smear and simple faecal flotation. Cats found positive for other parasitic and protozoal agents by faeces examination were excluded from the study. Complete blood counts (CBC) were performed with an automated blood cell counter for all cats. Blood smears were prepared (with May-Grunwald Giemsa) from samples, and the CBC results were confirmed microscopically (objective100x). White blood cell (WBC), neutrophil, lymphocyte and monocyte counts were recorded directly from the CBC. The neutrophil-to-lymphocyte ratio was calculated as the ratio of the absolute neutrophil count to the absolute lymphocyte count. The monocyte-to-lymphocyte was calculated as the absolute monocyte count ratio to the absolute lymphocyte count. White blood cell (P = 0.015), neutrophil (P = 0.001), monocyte (P = 0.033), NLR (P = 0.000) and MLR (P = 0.042) of diarrheal cats infected with Cystoisospora spp. were significantly higher than in the healthy group. There was no significant difference between groups in the lymphocyte counts (P > 0.05). SIRS (+) group had statistically significantly higher WBC (P = 0.014), neutrophil counts (P = 0.000), NLR (P = 0.000) and MLR (P = 0.037) than the healthy group. Also, neutrophil counts and NLR of the SIRS (+) group were statistically significantly higher than the SIRS (-) group (P = 0.032; P = 0.001, respectively). However, there was no significant difference SIRS (+), SIRS (-), and healthy groups regarding lymphocyte and monocyte counts (P > 0.05). The clinical severity of the disease positively correlated with NLR and MLR. Also, the best cut-off value of NLR to predict SIRS was > 1.67, with 92.86 % sensitivity and 84.62 % specificity. MLR was not a useful predictor for SIRS. Discussion: NLR and MLR are parameters derived from complete blood count. In recent years, they have been used in human and veterinary medicine as a biomarker in the diagnosis, prognosis and treatment follow-up of various diseases and provide valuable information about inflammation. In cats, there are limited studies on NLR, and to our knowledge, there are no studies on MLR. The current study suggests that NLR and MLR may be used to determine the severity of the inflammatory condition in diarrheal cats infected with Cystoisospora spp., and NLR is a useful marker for predicting SIRS status in these cats. In addition, this study also will contribute to larger-scale studies in the future. Keywords: cats, complete blood count, Cystoisospora, diarrhoea, NLR, MLR, SIRS.